2015
DOI: 10.1097/ijg.0b013e31829f99b7
|View full text |Cite
|
Sign up to set email alerts
|

Genotype-Phenotype Correlation in Moroccan Patients With Primary Congenital Glaucoma

Abstract: This is the first report of genotype-phenotype correlation in a large cohort of Moroccan PCG. Our results revealed that the worst phenotype and prognosis were observed in the double null CYP1B1 allele carriers followed by the nondouble null but other CYP1B1 mutations. This will contribute to the prediction of the prognosis of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…(5) Some sentences in the "Discussion" section have been deleted. (6) In Table 3: "Inbreeding" has been replaced by "Consanguinity". ( 7) All instances of "subjects" have been replaced by "patients".…”
Section: Declaration Of Conflicting Interestsmentioning
confidence: 99%
See 1 more Smart Citation
“…(5) Some sentences in the "Discussion" section have been deleted. (6) In Table 3: "Inbreeding" has been replaced by "Consanguinity". ( 7) All instances of "subjects" have been replaced by "patients".…”
Section: Declaration Of Conflicting Interestsmentioning
confidence: 99%
“…5 The clinical symptoms of increased IOP are: Enlargement of the globe (buphtalmos), Photophobia, Opacification of the cornea, epiphora and rupture in Descemet's membrane. 6 The diagnosis of PCG is based on medical conclusions: It is also Important to highlight that the genetic tests may also confirm the diagnosis. 7 This justifies the interest of the studies that have been carried out and those in progress to explain the correlation between genotype-phenotype and provide valuable regarding the underlying mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, mutations in the Cyp1b1 gene, in addition to being strongly related to the pathophysiology of PCG, are associated with the most severe disease outcomes. Notably, a genotype–phenotype study in a large cohort of Moroccan PCG reports that both patients carrying CYP1B1 mutation and those with double CYP1B1 null alleles showed the most severe phenotype when compared with patients genetically negative ( 156 ).…”
Section: Resultsmentioning
confidence: 99%
“…The incidence of PCG in Western countries (Ireland, Britain and USA) is 1 per 10–20,000 live births [ 3 ]. Recently, a genotype–phenotype study in a cohort of PCG patients in Morocco showed that disease severity, including mean intraocular pressure and number of surgeries, was significantly higher in the CYP1B1 mutation carriers as well as the double CYP1B1 null alleles [ 18 ]. Therefore, mutations in CYP1B1 are often associated with the most severe disease compared to other genes that are associated with the development of PCG [ 19 ].…”
Section: Resultsmentioning
confidence: 99%